Ossimoro e poesia: un percorso attraverso Montale, Caproni, Giudici e Zanzotto* - Bussolino, Claudia (Cuadernos de Filología Italiana, 2006)
This paper aims to find a path of meaning which is divided into two contrapositive directions beginning from a semantic field (all/nothing) through the language of four main protagonists of Twentieth Century (Montale, Caproni, Giudici, Zanzotto), considering particularly the books published during the Sixties and the Seventies. Besides the cases of real and effective oxymoron, this study tries to identify the cases of nagated antithesis, almost eliminated by the collocation of the words inside the versal metrical plot that interferes with the semantic level and the rhetoric level of a text, dinamically.
Keywords: Oxymoron; rhetorics and metrics; all/nothing